Implications of the Constitutional Court Decision Number 25/PUU-XIV/2016 on the Assessment of State Financial Losses in Corruption Cases of Public Procurement - Tomson Situmeang (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study analyzes the juridical implications of the Constitutional Court Decision Number 25/PUU-XIV/2016 concerning the assessment of state financial losses in corruption cases, particularly in public procurement. The decision asserts that only actual and verifiable financial losses (actual loss) may serve as valid legal evidence, thereby rejecting the use of potential or indicative losses (potential loss) as the sole basis for criminal liability. Employing a normative juridical method with statutory, conceptual, case, and comparative approaches, the study draws on primary data from relevant legislation, Constitutional Court and Supreme Court decisions, and institutional documents. Legal interpretation and doctrinal analysis were used to evaluate inconsistencies in judicial practice. The findings reveal that despite the Constitutional Court’s ruling, courts and prosecutors often continue to rely on investigative audit reports indicating potential losses without verifying actual harm. Such practices raise fundamental legal concerns regarding due process, the legality principle, and proportionality in sentencing. This study contributes to legal policy reform by proposing clearer evidentiary standards in corruption cases, offering practical insights for judges, prosecutors, state auditors, and legal scholars. Its novelty lies in reconstructing the legal framework for assessing state losses based on constitutional interpretation, distinguishing between actual and potential losses, and introducing a due process-oriented model for verification, causality, and proportional liability.